Enantioselective Aluminum-catalyzed Transformations using Chiral Organic Ligands. An Update - Pellissier, Hélène (Current Organic Chemistry, 2025)
Aluminum is the most abundant metal in the Earth’s crust and is the principal constituent of many common minerals. Taking advantage of its higher abundance and lower costs and toxicity compared with more traditional transition metals, this main group metal has emerged as a green metal of high potential and utility in organic synthesis. While many racemic aluminum catalysts have been early applied as Lewis acids to promote various reactions, such as Friedel-Crafts acylations, Alder-ene reactions, and polymerizations, chiral aluminum counterparts have been developed only since the 1990s in asymmetric catalysis. Indeed, the possibility of tuning the Lewis acidity of aluminum by making use of appropriate chiral ligands allows to control the stereoselectivity in a wide diversity of catalytic enantioselective reactions. For example, various types of ligands have been chelated to aluminum, such as salens, BINOL, and VANOL derivatives, TADDOL-derived ligands, cinchona alkaloids, and N,N’-dioxides. In the last decade, a wide variety of highly enantioselective aluminum-catalyzed transformations have been developed, spanning from basic reactions, such as cyanations of carbonyl compounds, aldol reactions, reductions, cycloadditions, cyclizations, α-alkylations of aldehydes, Michael additions, acyloin rearrangements, copolymerization etc., to more challenging and modern processes, such as domino and tandem reactions. The goal of this review is to collect the recent developments in enantioselective aluminum-catalyzed reactions of all types published since the beginning of 2015. It shows that asymmetric aluminum catalysis, which suits the growing demand for greener processes, offers a real opportunity to replace toxic and expensive metals soon.
Keywords: enantioselective reactions